CHARACTER ASSOCIATION STUDIES AMONG YIELD AND ITS COMPONENT CHARACTERS IN INDIAN MUSTARD (BRASSICA JUNCEA L. CZERN & COSS) - NEELAM SHEKHAWAT; G. C. JADEJA; JOGENDRA SINGH; RAVINDRA SINGH SHEKHAWAT (The Bioscan, 2014)
Sixty genotypes of Indian mustard (Brassica juncea L. Czern and Coss) were evaluated in randomized block design with two replications during 2011-2012 rabi season to study character association for 13 yield and its component characters. There was positive, significant and strong correlation of seed yield per plant with number of siliqua per plant (rg=0.799 and rp=0.782), test weight (rg=0.596 and rp=0.588) and number of seeds per siliqua (rg=0.299 and rp=0.320) while, it was negatively and significantly correlated with days to 50% flowering (rg= -0.368 and rp= -0.282) and days to maturity (rg= -0.308 and rp= -0.253). Out of these characters, days to 50% flowering was significantly and positively correlated with days to maturity (rg=0.611 and rp=0.472) and it was also correlated significantly with test weight (rg= -0.288) but in negative sense and at genotypic level only, while correlation between days to maturity and number of seeds per siliqua (rg= -0.343 and rp= -0.275) was negative and significant. According to path analysis, number of siliqua per plant (0.694), test weight (0.509) and number of seeds per siliqua (0.470) have positive and high direct effects with seed yield per plant, indicating importance of these characters and can be strategically used to improve the seed yield per plant of Indian mustard.